La naturaleza del bien común político en Santo Tomás de Aquino y la aparición de una errónea formulación contemporánea. - Castaño, Sergio Raúl (Scripta Mediaevalia, 2025)
The aim of this article is to outline the broad lines of the relationship between the political common good and the particular good in Aquinas; furthermore, to show the infeasibility of formulating a definition of the political common good ad mentem Sancti Thomae according to the liberal-individualist approach of the set of conditions for the perfection of the person; and, finally, to detect some appearances of this formula and its antecedents within the doctrine of Thomist philosophers and theologians of the first half of the 20th century.